How Marketisation and Privatisation Is Being Used to Abolish National Universal Health Care Systems and What Must Be Done to Restore Them - Pollock, Allyson M. (Revista del CLAD Reforma y Democracia, 2016)
The decision to have a universal public health care system is always political. Many countries have decided that universal health care is the hallmark of a civilized society and that it is both necessary and affordable for governments to legislate for its citizens to that end. The question of how much any country should spend is inextricably linked to the chosen model of funding and provision, the degree of marketisation and how much risk selection and denial of care a government is prepared to tolerate in its health system.There is no country in the world that has delivered universal health care through a market and for-profit provision. This is because markets operate through selection and exclusion, transferring risks and costs back to the users of services and denying care to those that need them most. Risk selection and exclusion is built into the design of market administration; in contrast, inclusion and redistribution must be built into the systems of public administration for universal health systems. This paper takes the examples of medicines, public private partnerships and two health systems (UK and US) to show how risk selection and avoidance undermines the goal of access and universality.The US, with health expenditure of around 18% of GDP denies more than one in five of its population access to health care. Overtreatment and denial of care, catastrophic costs and spiraling health expenditure are the hallmark of US health care. Those countries that have adopted the US model of mixed funding and private provision have more marketisation, higher administration costs, the greatest inequalities in access, lack of coverage, and highest out of pocket payments.The UK put in place its National Health Service in 1948, as a universal integrated public health system free at the point of delivery and funded through central taxation. This became the model for many countries’ health systems across the world, the UK NHS had the lowest cost, most efficient and fairest system, guaranteeing health care to all its citizens without fear of catastrophic health care costs or being denied care. In 2012, following two decades of market incrementalism, the government in England abolished the universal public model replacing it with the non-universal US market risk selection mechanisms with catastrophic consequences. Scotland and Wales have retained the universal public NHS model.If universal health care is our goal, we need first to understand how the principles of public health need, redistribution, and risk-pooling or social solidarity are alienated by markets and marketisation. If the law commits a government to provide universal health car to its citizens, it is the task of the administrative bureaucracy to determine how the functions will be implemented and whether the goals will be achieved. Access to universal health care requires strong systems of public administration which must adhere to common principles: fairness of financing, fairness of resource allocation, risk pooling and social solidarity in service provision, political accountability and control, service integration through geographic units of administration, and public accountability through strong systems of information and surveillance systems. These are the necessary first steps towards the Sustainable Development Goals for universal health care and access to rational and essential medicines.
Keywords: Health Policy; Privatization; Health Services; Protection of Health; Medicinal Drugs